Enhancement of innate immunity in gingival epithelial cells by vitamin D and HDAC inhibitors - Figgins, Erika L.; Arora, Payal; Gao, Denny; Porcelli, Emily; Ahmed, Rabab; Daep, Carlo Amorin; Keele, Garrett; Ryan, Lisa K.; Diamond, Gill (Frontiers in Oral Health, 2024)
Introduction The human host defense peptide LL-37 is a component of the innate immune defense mechanisms of the oral cavity against colonization by microbes associated with periodontal disease. We have previously shown that the active form of vitamin D, 1,25(OH)2D3, can induce the expression of LL-37 in gingival epithelial cells (GEC), and prevent the invasion and growth of periopathogenic bacteria in these cells. Further, experimental vitamin D deficiency resulted in increased gingival inflammation and alveolar bone loss. Epidemiological studies have shown associations between vitamin D deficiency and periodontal disease in humans, suggesting application of vitamin D could be a useful therapeutic approach. Further, since we have shown the local activation of vitamin D by enzymes expressed in the GEC, we hypothesized that we could observe this enhancement with the stable, and inexpensive inactive form of vitamin D, which could be further increased with epigenetic regulators. Methods We treated 3-dimensional primary cultures of GEC topically with the inactive form of vitamin D, in the presence and absence of selected histone deacetylase (HDAC) inhibitors. LL-37 mRNA levels were quantified by quantitative RT-PCR, and inhibition of invasion of bacteria was measured by fluorescence microscopy. Results Vitamin D treatment led to an induction of LL-37 mRNA levels, as well as an inhibition of pro-inflammatory cytokine secretion. This effect was further enhanced by HDAC inhibitors, most strongly when the HDAC inhibitor, phenyl butyrate (PBA) was combined with Vitamin D3. This was observed both in solution and in a prototype gel formulation using sodium butyrate. Finally, this combination treatment led to an increase in the antimicrobial activity against infection by Porphyromonas gingivalis and Filifactor alocis, bacteria associated with periodontal lesions, as well as herpes simplex virus, which has also been shown to be associated with periodontal lesions. Conclusions Our results demonstrate that a combination of inactive vitamin D and sodium butyrate could be developed as a safe treatment for periodontal disease.